2015
DOI: 10.3109/10253890.2015.1045868
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction and heart rate variability in depression

Abstract: Depression occurs in people of all ages across all world regions; it is the second leading cause of disability and its global burden increased by 37.5% between 1990 and 2010. Autonomic changes are often found in altered mood states and appear to be a central biological substrate linking depression to a number of physical dysfunctions. Alterations of autonomic nervous system functioning that promotes vagal withdrawal are reflected in reductions of heart rate variability (HRV) indexes. Reduced HRV characterizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
172
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(183 citation statements)
references
References 93 publications
6
172
0
5
Order By: Relevance
“…While the cross-sectional nature of this study does not allow definitive determination of causality, the consistent lower values of HRV shown here suggests that total cumulative stress, with its components of chronic stress and cumulative adverse life events, may contribute to a state of cardiac ANS dysfunction, independent of any existent mental or physical disease state. While prior studies have shown the effects of single specific stressors on HRV, including work stress, anxiety, low socioeconomic status, and depression (20, 21, 31, 5658), this is the first to show that cumulative stress over the lifespan, as measured by the CAI total score, is associated with reduced HRV.…”
Section: Discussionmentioning
confidence: 62%
“…While the cross-sectional nature of this study does not allow definitive determination of causality, the consistent lower values of HRV shown here suggests that total cumulative stress, with its components of chronic stress and cumulative adverse life events, may contribute to a state of cardiac ANS dysfunction, independent of any existent mental or physical disease state. While prior studies have shown the effects of single specific stressors on HRV, including work stress, anxiety, low socioeconomic status, and depression (20, 21, 31, 5658), this is the first to show that cumulative stress over the lifespan, as measured by the CAI total score, is associated with reduced HRV.…”
Section: Discussionmentioning
confidence: 62%
“…Further studies have since documented adverse prognostic implications of reduced HRV in MI patients (Cripps et al, 1991; Tsuji et al, 1996; Boskovic et al, 2014; Song et al, 2014). Psychosocial factors, such as stressful life events (Pieper et al, 2010; van Ockenburg et al, 2015), general stress (Kang et al, 2004; Brosschot et al, 2006; Chandola et al, 2010; Chida and Steptoe, 2010), hostility (Virtanen et al, 2003; Chida and Steptoe, 2009), depression (Stein et al, 2000; Gehi et al, 2005; Ha et al, 2015; Sgoifo et al, 2015) and anxiety (Friedman and Thayer, 1998; Alvares et al, 2013) have all been found to be associated with lowered HRV. In addition, individuals with stronger emotion regulation (Thayer et al, 2009; Patron et al, 2014; Gillie et al, 2015) and adaptive coping strategies have been shown to have higher levels of HRV (Appelhans and Luecken, 2008; Thayer and Lane, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In cardiac patients, illness perceptions, including loss of perceived control, negative emotional responses and greater consequences have variously been shown to be associated with psychological distress, such as anxiety and depressive symptoms (Sherry et al, 2005). Moreover, a range of psychosocial factors, including depression (Stein et al, 2000; Gehi et al, 2005; Ha et al, 2015; Sgoifo et al, 2015) and anxiety (Friedman and Thayer, 1998; Alvares et al, 2013), but also stressful life events (Pieper et al, 2010; van Ockenburg et al, 2015), general stress (Kang et al, 2004; Brosschot et al, 2006; Chandola et al, 2010; Chida and Steptoe, 2010) and hostility have all been found to be associated with lowered HRV. In addition, negative illness perceptions are associated with maladaptive health behaviors, such as lack in physical activity, which in turn might contribute to lower HRV.…”
Section: Introductionmentioning
confidence: 99%
“…Subjects with depression and anxiety disorders exhibit abnormal HRV patterns compared with non-psychiatric controls (Servant et al, 2009). Reduced HRV characterizes emotional dysregulation, decreased psychological flexibility and defective social engagement, which in turn are linked to prefrontal cortex hypoactivity (Sgoifo et al, 2015). High occupational stress has also been associated with lowered HRV, specifically with reduced parasympathetic activation.…”
Section: Non-medical Treatment Of Cardiac Autonomic Neuropathymentioning
confidence: 99%